Validity and reliability study of Turkish form of substance use awareness and insight scale - Karakaş, Mehmet; Koç, Ayşegül (Journal of Dependence, 2025)
Objective: The aim of this study was to test the reliability and validity of the Turkish version of the Substance Use Awareness and Insight Scale. Method: The sample of the study consisted of 101 inpatients with a diagnosis of substance use disorder admitted to a mental health and diseases hospital. The research data were collected with ‘Patient Introduction Form’, ‘Substance Use Awareness and Insight Scale’ and ‘Addiction Profile Index Effects on Life subscale and Motivation subscale’. The scale was tested with validity and reliability analyses such as exploratory factor analysis after language validity, confirmatory factor analysis, criterion validity, item discrimination and Cronbach Alpha coefficient. Results: The results of the internal consistency analyses showed that the factor loadings of the scale were between 0.53 and 0.80. The scale has two sub-dimensions as disease awareness and awareness of negative consequences, and Cronbach Alpha values were 0.716 and 0.689, respectively. The total Cronbach Alpha value of the scale was found to be 0.758. In the confirmatory factor analysis, χ2/Sd=1.705, GFI=0.949, AGFI=0.869, CFI=0.945, RMSEA=0.080, SRMR=0,096. There was a positive and significant relationship between the Substance Use Awareness and Insight Scale and the Addiction Profile Index Motivation and Effects on Life sub-dimensions. Conclusion: The Turkish form of the Substance Use Awareness and Insight Scale was found to be a valid and reliable measurement tool with seven items and a two-factor structure, based on short and self-report.